Is populism a challenge to European energy and climate policy? Empirical evidence across varieties of populism. Issue 7 (3rd July 2021) - Huber, Robert A.; Maltby, Tomas; Szulecki, Kacper; Ćetković, Stefan
ABSTRACT: Despite the burgeoning literature, evidence on how right-wing populists frame and act on energy and climate issues is limited and even more scarce for other types of populist parties. We address this gap by exploring the policy discourses, positions and actions of six European populist parties from Austria, Czechia, Greece, Italy, Poland and Spain belonging to different types of populism. We argue that there is substantial and largely neglected variation among different populist parties in their approach to and effects on EU energy and climate policy (ECP). We find support for the notion that right-wing and right-leaning valence populist parties are at odds with ambitious EU ECP. On the contrary, the analysed left-wing and left-leaning valence populists rely on populist discourses to demand more ambitious ECP measures. Furthermore, our analysis suggests that participation in government decreases the role of populism in parties' ECP discourse and dilutes parties' positions and actions.